THE USE OF QUIZIZZ AND KAHOOT! IN THE TRAINING FOR MILLENNIAL GENERATION - Agus Suharsono (IJIET (International Journal of Indonesian Education and Teaching), 2020)
Digital transformation marked with internet and information technology use has entered into government apparatus learning, particularly the new employees constituting millennial generation inherent to gadget. Kahoot! and Quizizz are online quiz application that can be the choice to make the learning attractive and joyful. This research employed a quasi-experimental method only on the studied group, and the data was collected using questionnaire, observation, and documentation. Data was analyzed using logico-inductive method encompassing thee stages: coding, describing main characteristics and interpreting data. The result of research showed that Quizizz is more preferable to Kahoot! to the participants because in Quizizz question and answer appear on cell phone/laptop screen of individual participants so that they should not see the screen before the class just like that in Kahoot!; the answer in Kahoot! constitutes symbols while in Quizizz the real answer constitutes word, number, or figure; after the quiz has been completed, the questions answered can be checked in order to find out the ones answered incorrectly and mastered poorly by the participants.